Balance assessment in people with chronic obstructive pulmonary disease - Michelle Difante Pedrozo; Aron Ferreira da Silveira
Introduction Body balance is one of the most important functions of the organism and is directly associated with quality of life. Thus, given that chronic obstructive pulmonary disease (COPD) causes pulmorary alterations as well as several systemic complications, it is extremely important to make a careful investigation of its implications for body stability. Objective To assess the balance of individuals with COPD by using Foam-Laser Dynamic Posturography. Materials and methods 29 patients (19 men and 10 women; mean age 64.72 ± 7.67 years) who were former smokers and had COPD GOLD II and III were selected to participate in the study group. The control group was composed of 24 individuals (12 women and 12 men; mean age 63.58 ± 8.17 years) who did not have COPD. To assess the balance of participants, we used Foam-Laser Dynamic Posturography. Results With regard to the Foam-Laser Dynamic Posturography test, we found no significant differences (p < 0.05) between the experimental and the control group when compared to the variables of the SOT tests (SOT I to VI) or to the variables of the sensory analysis, i.e., somatosensory, visual and vestibular functions, and visual preference. Conclusion This study demonstrated that subjects with and without COPD showed a similar performance in the Foam-Laser Dynamic Posturography test.